Exploratory Investigation of the Effects of Perspective Taking and Awareness of Vulnerability on Impressions of Robots - Ikeda, S. (Social Psychology and Society, 2024)
Abstract only Objective. This exploratory study investigated whether perspective-taking and awareness of vulnerability procedures could enhance impressions of robots. Background. A society characterized by the harmonious coexistence of humans and robots is poised for realization in the imminent future. Nevertheless, numerous challenges must be confronted for the materialization of such a societal paradigm. One among them pertains to the prevailing tendency for humans to harbor adverse perceptions of robots, the amelioration of which proves to be a complex endeavor. The present study undertakes an exploratory investigation into strategies aimed at mitigating unfavorable impressions associated with robots. Study design. Participants were randomly assigned to one of three groups: control group, perspective perception group, and robot vulnerability awareness group, and received different instructions. Participants. Online experiments were conducted with 360 participants who were asked to imagine and describe a day in the life of a robot, and their impressions of the robot were measured using a questionnaire. Measurements. Upon conjecturing and articulating the robot's daily routines, participants shared their perceptions of the robot through the application of three assessment tools: the Robot Anxiety Scale, the Mind Attribution Scale, and the Familiarity Rating Scale. Results. The manipulation checks confirmed successful manipulation, but there was no evidence that perspective-taking or awareness of vulnerability influenced impressions of the robot. Conclusions. The efficacy of perspective-taking, a technique established as beneficial in ameliorating adverse perceptions of humans, may exhibit diminished effectiveness in the context of alleviating negative impressions associated with robots. Цель. Поиск ответа на вопрос о том, приведут ли децентрация (стремление понять опыт и точку зрения других) и повышение осведомленности об уязвимости робота к изменению восприятия человеком роботов. Контекст и актуальность. Общество, характеризующееся гармоничным сосуществованием людей и роботов, готово к реализации важнейших задач, стоящих перед ближайшим будущим человечества. Тем не менее для материализации такой парадигмы необходимо решение множества проблем, одна из которых связана с преобладанием у людей негативного восприятия роботов. Настоящее исследование посвящено изучению стратегий, направленных на смягчение неблагоприятных впечатлений, возникающих у людей при взаимодействии с роботами. Дизайн исследования. Участники были случайным образом распределены в одну из трех групп: контрольную группу, группу «децентрации» и группу осознания уязвимости роботов и получили различные инструкции. Участники должны были представить и описать один день из жизни робота, а их впечатления от робота измерялись с помощью анкеты. Участники. В онлайн-эксперименте приняли участие 360 человек. Методы (инструменты). Свободное описание распорядка дня робота; три оценочных инструмента: Шкалы тревожности робота, Шкалы атрибуции разума и Шкалы оценки знакомства. Результаты. Проверка подтвердила успешность манипуляций, но не было обнаружено никаких доказательств того, что «децентрация», т.е. стремление понять опыт и точку зрения других, или осознание уязвимости повлияли на впечатления людей о роботах. Выводы. Эффективность метода «децентрации», признанного полезным для смягчения негативных представлений о людях, демонстрируют меньшую эффективность при смягчении негативных впечатлений, связанных с роботами.